The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1073/pnas.0400610101
|View full text |Cite
|
Sign up to set email alerts
|

Defective development of splenic and epidermal CD4+dendritic cells in mice deficient for IFN regulatory factor-2

Abstract: Dendritic cells (DCs) play important roles in the initiation and regulation of immune responses. Although several subsets of DCs were identified according to their expression of surface molecules such as CD4, CD8, and CD11b, the regulatory mechanism for the development and homeostasis of these DC subsets remains unclear. Here we show that mice lacking IFN regulatory factor-2 (IRF-2 ؊/؊ mice) exhibited a marked and selective defect in splenic CD4 ؉ CD11b ؉ DCs, instead of CD8␣ ؉ CD11b ؊ DCs that were reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 42 publications
5
90
0
1
Order By: Relevance
“…Consistent with this report, previous studies have shown that RelB, like IRF-4, is expressed in myeloid DC, and is required for the development of CD4 + DC [2,15,16]. In addition to the above IRFs, IRF-2 is reported to be required for the development of CD4 + DCs [17,18]. Interestingly, IRF-2 acts by inhibiting IFNa/β suppression of DC development.…”
Section: Subset Development Specified By Irf-8 and Irf-4supporting
confidence: 76%
“…Consistent with this report, previous studies have shown that RelB, like IRF-4, is expressed in myeloid DC, and is required for the development of CD4 + DC [2,15,16]. In addition to the above IRFs, IRF-2 is reported to be required for the development of CD4 + DCs [17,18]. Interestingly, IRF-2 acts by inhibiting IFNa/β suppression of DC development.…”
Section: Subset Development Specified By Irf-8 and Irf-4supporting
confidence: 76%
“…Other genes, i.e. Krüppel family of zinc finger transcription factor Ikaros C, transcription factor PU.1, IRF-2 and IRF-4 (IFN regulatory factor-2 and -4), Notch-dependent transcription factor RBP-J, and TRAF6 (TNF receptor associated factor-6), have also been described to play a role in differentiation of CD4+ DC subset [36][37][38][39][40][41]. The Ig superfamily member, CD40 and Toll-like receptors are receptors known to signal through TRAF6, yet none of those TNFR are implicated in the regulation of DC homeostasis.…”
Section: Noncanonical Nfκb Signaling Cascade Regulates DC Homeostasismentioning
confidence: 99%
“…Transcription factors of the IFN regulatory factor (IRF) family play crucial roles in differentiation as well as in the functional activity of DCs. GM-CSF-dependent development of DCs depends on IRF4 (46), as well as IRF2 (47,48). In addition, RelB, a member of the NF-B family, is required for the development of some subsets of DCs (49,50).…”
Section: Tsa Blocks Gm-csf-dependent Differentiation To Dcsmentioning
confidence: 99%